2016
DOI: 10.1038/cr.2016.57
|View full text |Cite
|
Sign up to set email alerts
|

Grafting voltage and pharmacological sensitivity in potassium channels

Abstract: A classical voltage-gated ion channel consists of four voltage-sensing domains (VSDs). However, the roles of each VSD in the channels remain elusive. We developed a GVTDT (Graft VSD To Dimeric TASK3 channels that lack endogenous VSDs) strategy to produce voltage-gated channels with a reduced number of VSDs. TASK3 channels exhibit a high host tolerance to VSDs of various voltage-gated ion channels without interfering with the intrinsic properties of the TASK3 selectivity filter. The constructed channels, exempl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…S2 C and D). To test if this result derives from a specificity of C28 to the KCNQ1 VSD, we studied the KTQ and KTV channels, which are comprised of the twopore-domain channel TWIK-related, acid-sensitive K + 3 (TASK3) fused with the KCNQ1 and K V 1.2 VSD, respectively (38). TASK3 itself lacks a VSD so that its opening is not dependent on voltage (39), but Lan et al (38) demonstrated that the fused VSD induces voltage-dependent gating in the KTQ and KTV channels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2 C and D). To test if this result derives from a specificity of C28 to the KCNQ1 VSD, we studied the KTQ and KTV channels, which are comprised of the twopore-domain channel TWIK-related, acid-sensitive K + 3 (TASK3) fused with the KCNQ1 and K V 1.2 VSD, respectively (38). TASK3 itself lacks a VSD so that its opening is not dependent on voltage (39), but Lan et al (38) demonstrated that the fused VSD induces voltage-dependent gating in the KTQ and KTV channels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, we found that, unlike its action on KCNQ1, C28 did not alter voltage dependent activation of the Shaker K + channel (Fig S2C, D). To test if this result derives from a specificity of C28 to the KCNQ1 VSD, we studied the KTQ and KTV channels, which are comprised of the two-pore-domain channel TASK3 fused with the KCNQ1 and KV1.2 VSD, respectively(38). TASK3 itself lacks a VSD so that its opening is not dependent on voltage(39), but Lan et al(38) demonstrated that the fused VSD induces voltage dependent gating in the KTQ and KTV channels (Fig 4A-D).…”
Section: Resultsmentioning
confidence: 99%
“…To test if this result derives from a specificity of C28 to the KCNQ1 VSD, we studied the KTQ and KTV channels, which are comprised of the two-pore-domain channel TASK3 fused with the KCNQ1 and KV1.2 VSD, respectively(38). TASK3 itself lacks a VSD so that its opening is not dependent on voltage(39), but Lan et al(38) demonstrated that the fused VSD induces voltage dependent gating in the KTQ and KTV channels (Fig 4A-D). We found that C28 shifted voltage dependent activation of the KTQ channel, which is comprised of TASK3 fused with the KCNQ1 VSD, to more negative voltages and suppressed the amplitude of the current (Fig 4A, B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations